Effects of Waves and Sediment Disturbance on Seed Bank Persistence at Tidal Flats - Zhu, Zhenchang; Bouma, Tjeerd J.; Zhu, Qin; Cai, Yanpeng; Yang, Zhifeng (Frontiers in Marine Science, 2021)
Coastal wetlands such as salt marshes have been increasingly valued for their capacity to buffer global climate change effects, yet their long-term persistence is threatened by environmental changes. Whereas, previous studies largely focused on lateral erosion risk induced by stressors like sea level rise, it remains poorly understood of the response of lateral expansion to changing environments. Seedling establishment is a key process governing lateral marsh expansion as seen in many coastal regions such as Europe and East Asia. Here, we evaluate mechanistically the response of seed bank dynamics to changing physical disturbance at tidal flats, using the globally common coastal foundation plant, cordgrass as a model. We conducted a large-scale field study in an estuary in Northwest Europe, where seed bank dynamics of cordgrass in the tidal flats was determined and linked to in situ hydrodynamics and sediment dynamics. The results revealed that wave disturbance reduced the persistence of seeds on the surface, whereas amplified sediment disturbance lowered the persistence of both surface and buried seeds. Overall, this indicates that increasing storminess and associated sediment variability under climate change threatens seed bank persistence in tidal flats, and hence need urgently be incorporated into models for long-term bio-geomorphological development of vegetated coastal ecosystems. The knowledge gained here provides a basis for more accurate predictions on how climatically driven environmental changes may alter the fitness, resilience and persistence of coastal foundation plants, with significant implications for nature-based solutions with coastal vegetation to mitigate climate change effects.